1990
DOI: 10.1161/01.cir.81.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Relation of blood viscosity to demographic and physiologic variables and to cardiovascular risk factors in apparently normal adults.

Abstract: Although increased blood viscosity occurs in several cardiovascular diseases, little is known of factors influencing blood rheology in normal adults. Accordingly, we examined the relations of whole blood viscosity (WBV) to its rheologic determinants (hematocrit level, plasma viscosity, protein concentration, and red cell aggregability and rigidity), to demographic and laboratory variables, and to cardiovascular risk factors in 128 normotensive employed adults. Hematocrit levels accounted for 67-84% of variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
203
1
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(232 citation statements)
references
References 56 publications
(12 reference statements)
13
203
1
7
Order By: Relevance
“…One study indicated that, compared to a control with diastolic BP (DBP) than with systolic BP (SBP). [27][28][29][30]32 This is consistent with the contribution group of 24 subjects, 45 patients with mild hypertension had similar haematocrit, red blood cell mass of the haematocrit, and hence blood viscosity, to peripheral vascular resistance, which is a determiand plasma volume levels. In contrast, 43 other subjects with moderate to severe hypertension had a nant of DBP.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…One study indicated that, compared to a control with diastolic BP (DBP) than with systolic BP (SBP). [27][28][29][30]32 This is consistent with the contribution group of 24 subjects, 45 patients with mild hypertension had similar haematocrit, red blood cell mass of the haematocrit, and hence blood viscosity, to peripheral vascular resistance, which is a determiand plasma volume levels. In contrast, 43 other subjects with moderate to severe hypertension had a nant of DBP.…”
supporting
confidence: 71%
“…Table 2 shows that significant correlations number of subjects. In contrast, one recent paper by Vayá et al 18 noted no difference in haematocrit level between BP and haematocrit have been reported in a range of population studies, [26][27][28][29][30][31][32][33] although this does when comparing a group of 21 hypertensives with a group of controls, which agreed with some earlier not seem to be true among hypertensive patients, 34 possibly due to the effects of treatment and/or renal reports. 11, 20 An increased haematocrit among hypertensives could be due to either an increase in red impairment.…”
mentioning
confidence: 95%
“…This effect is likely to be, in part, attributable to favourable effects on serum lipids and haemostatic factors [3,5,13]. Haematocrit, which is an independent risk factor for vascular disease [14][15][16][17] perhaps by influencing blood viscosity [18] and erythrocyte-mediated platelet adhesion [19], has not been assessed in previous studies of the response of cardiovascular risk factors to tamoxifen. Our data demonstrate that tamoxifen prevents the age-related increase in haematocrit which occurs in postmenopausal women [17], and which was observed in the placebotreated women in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Furthermore, relationships have been reported between blood viscosity and some cardiovascular risk factors, such as hypertension, dyslipidemia, smoking, and obesity. [11][12][13][14] An increase in blood viscosity has been identified in the acute phase of ischemic stroke, similar to other thrombotic diseases. [15][16][17][18][19] However, actual 4 measurements of blood viscosity have not been performed because of the stereotypical belief that blood viscosity increases equally in all ischemic stroke subtypes, which is within expectations and with less clinical value.…”
Section: Introductionmentioning
confidence: 94%